Association between Working Duration and Hemoglobin Levels among Parking Attendants at Gondanglegi Market, Malang Regency - Aina Salma Hikmatul Maula; Yeni Avidhatul Husnah; Previta Zeizar Rahmawati (poltekkes kemenkes pontianak, 2026)
Hemoglobin (Hb) is an essential parameter in oxygen transport and can be affected by occupational and environmental factors, including working duration. Parking attendants at Gondanglegi Market, Malang Regency, are exposed to prolonged working hours, vehicle emissions, and high physical activity, which may contribute to decreased hemoglobin levels. Previous studies have reported that occupational exposure to air pollution and long-term workload may negatively influence hematological status. However, studies focusing on hemoglobin levels among informal sector workers, particularly parking attendants, remain limited. This study aimed to analyze the hemoglobin levels of parking attendants based on their working duration at Gondanglegi Market, Malang Regency. A descriptive quantitative study design was employed using a total sampling technique involving 25 respondents. Blood samples were collected from parking attendants, and hemoglobin levels were measured using a photometer with the Cyanmethemoglobin method at the Bululawang Public Health Center Laboratory. The findings revealed that most respondents with a working duration of less than 10 years had normal hemoglobin levels, whereas respondents with more than 10 years of service tended to have hemoglobin levels below the normal range. These findings indicate that prolonged occupational exposure and longer working duration may contribute to decreased hemoglobin levels among parking attendants.